Cross-junction traffic control system via sensor feedback - Fouzy, Ahmad Shafeeq August; Nawawi, Sophan Wahyudi; Ramli, Muhammad Ruzairi; Leong, Yong Liang; Nian, Noel Ng Fong; Abas, Khairul Hamimah; Abdul Shaib, Mohd. Fadzli (Penerbit UTHM, 2022)
There are two types of junctions at the highways. One of the designs is two main roads are grade-separated and is called an interchange. All designs are to ensure continuous traffic flow. Examples of the two most common types of highway interchanges are shown in Figure 7.1. An at-grade junction is called an intersection. Cross intersections with traffic light control are found everywhere within an urban area where vehicles are abundant. It's can also be found at the exit of a highway, where it connects to a local road. The cross intersection Sensor & Instrumentation System Series 28 ISBN 978-967-2817-62-8 2022 90 commonly being constructed below or above a highway depending on the type of land or terrain. The most common type of such cross intersection in Malaysia are illustrated in Figure 7.2.